A Security Framework for Distributed Ledgers - Graf, Mike; Rausch, Daniel; Ronge, Viktoria; Egger, Christoph; Küsters, Ralf; Schröder, Dominique (CCS '21, 2021)
In the past few years blockchains have been a major focus for security research, resulting in significant progress in the design, formalization, and analysis of blockchain protocols. However, the more general class of distributed ledgers, which includes not just blockchains but also prominent non-blockchain protocols, such as Corda and OmniLedger, cannot be covered by the state-of-the-art in the security literature yet. These distributed ledgers often break with traditional blockchain paradigms, such as block structures to store data, system-wide consensus, or global consistency. In this paper, we close this gap by proposing the first framework for defining and analyzing the security of general distributed ledgers, with an ideal distributed ledger functionality, called Fledger, at the core of our contribution. This functionality covers not only classical blockchains but also non-blockchain distributed ledgers in a unified way. To illustrate Fledger, we first show that the prominent ideal block-chain functionalities Gledger and GPL realize (suitable instantiations of) Fledger, which captures their security properties. This implies that their respective implementations, including Bitcoin, Ouroboros Genesis, and Ouroboros Crypsinous, realize Fledger as well. Secondly, we demonstrate that Fledger is capable of precisely modeling also non-blockchain distributed ledgers by performing the first formal security analysis of such a distributed ledger, namely the prominent Corda protocol. Due to the wide spread use of Corda in industry, in particular the financial sector, this analysis is of independent interest. These results also illustrate that Fledger not just generalizes the modular treatment of blockchains to distributed ledgers, but moreover helps to unify existing result
Keywords: Distributed Ledgers; Blockchain; Universal Composability; ProtocolSecurity; Corda